(untitled) (Research, Society and Development, 2021)
Snacks obtained by extrusion can be added with agro-industrial by-products, a low-cost alternative to increase nutritional value, and Spirulina platensis (SP), a source of proteins and antioxidants. In this study, extruded snacks were developed using a 2² experimental design where variables S. platensis (SP) - 2.5 to 7.5 g.100 g-1 and feed moisture (M) - 18 to 26 g.100 g-1 were tested. The formulations were composed of rice (Oryza sativa) flour (72.5 to 77.5 g.100g-1) and 20 g.100g-1 of a mixture flour of orange (Citrus sinensis L. Osbeck) and peach palm (Bactris gasipaes) by-products (1:1). Snacks were evaluated for nutritional, technological and sensory parameters. It was found that SP increased the protein and antioxidant content of the formulations. When compared to a similar commercial product, snacks contained 15-48% more protein, and 320-380% more dietary fiber. The increase in SP increased the antioxidant activity of snacks by more than 1000%. In the tested conditions, the apparent density was directly proportional to U, while hardness and crunchiness were inversely proportional. However, the SP and U variables did not affect the expansion rates, water solubility, water absorption and oil absorption. The highest sensory acceptance, of 72 and 73%, occurred in a condition of greater incorporation of SP. Thus, the possibility of making gluten-free snacks with a higher nutritional value than those marketed was shown, for consumers aware of a healthier diet, as well as an alternative for the use of by-products.